Technologies for non-invasive physiological sensing: Status, challenges, and future horizons - Yu, Yang; Jain, Bhavya; Anand, Gautam; Heidarian, Mahdi; Lowe, Andrew; Kalra, Anubha (Biosensors and bioelectronics. X, 2024)
Non-invasive techniques have become increasingly vital in modern medicine, providing valuable diagnostic information without invasive procedures. These techniques encompass a diverse range of procedures, including imaging scans, blood tests, urine tests, and genetic testing, enabling the investigation of various conditions without device insertion. In contrast to conventional invasive methods, non-invasive diagnostics have numerous advantages, including reduced complications, shorter recovery times, improved patient comfort, and lower costs. As a result, the exploration of alternative diagnostic approaches has become imperative. This article provides a comprehensive overview of advances, challenges, and opportunities in the realm of non-invasive diagnostic techniques. It delves into a detailed exploration of non-invasive techniques, including photoplethysmography (PPG), electroencephalography (EEG), electromyography (EMG), electrocardiography (ECG), computed tomography (CT), magnetic resonance imaging (MRI), ultrasound (US), and electrical impedance tomography (EIT) discussing their origin, underlying principles, instrumentation, and applications in various medical fields. Furthermore, the advantages and limitations of various Surface Measurement and Imaging Modalities techniques are thoroughly compared and analysed. The article also addresses these challenges and highlights emerging technologies and methodologies that offer solutions. More importantly, we propose several promising directions for future research and development of non-invasive diagnostic techniques.